Accompanying the making of yoghurt for Selagalih Families Ciomas Rahayu Village, Bogor Regency - Oom Komala (International Journal of Business, Economics, and Social Development, 2020)
Ciomas Rahayu Village, Bogor Regency is an area with populated densely. Knowledge of the benefits and making of Yoghurt for moms of family welfare coaching is very important. Because Yoghurt has been shown to improve the body's immune system and overcome lactose intolerance. The purpose of this program was provide counseling and accompanying about the making of yoghurt for the family as well as explanation of the benefits of yoghurt if consumed.  Activity method was practice in making yoghurt from basic ingredients of milk and were given starter to be fermented by moms of family welfare coaching Ciomas Rahayu Village Bogor Regency on 30 people cadres. Milk was fermented  in a bottle is done for 2 x 24 hours at a temperature of  37oC-42oC. Fermentation results were  added sugar  expected can make the family business knowledge. Evaluation of Yoghurt production results done that moms can make yoghurt well so that result satisfactory. To do business need existence of cooperation with other party funding. Outcome of this activity was the increasing understanding and skill of partner of Ciomas Rahayu Village, Bogor Regency in making Yoghurt and increasing family business skill.